2001
DOI: 10.1515/cclm.2001.141
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Serum Cystatin C: Biological Variation and Reference Values

Abstract: Human cystatin C is a low molecular weight protein which has been proposed as a better marker of glomerular filtration rate than creatinine. To be able to interpret results obtained in different patient populations it is necessary to define cystatin C reference values. We measured serum concentration of cystatin C in 1223 subjects using a particle-enhanced nephelometric assay. Subjects were aged 4 to 79 years and were selected among apparently healthy individuals who came to the Centre for Preventive Medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
4
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 33 publications
11
76
4
12
Order By: Relevance
“…Amongst the extra renal factors which may influence CysC values in healthy people, the most recent work has shown that in adults under 60 years old, CysC concentrations are lower in women than in men, the difference disappearing over the age of 60 years old (30)(31)(32). These results contradict the older studies which did not recommend establishing sex-related reference values (24,(33)(34)(35)(36)(37), except for results found by Pergande and Jung (38).…”
Section: Physiological Determinants Of Cysc Productionmentioning
confidence: 89%
See 2 more Smart Citations
“…Amongst the extra renal factors which may influence CysC values in healthy people, the most recent work has shown that in adults under 60 years old, CysC concentrations are lower in women than in men, the difference disappearing over the age of 60 years old (30)(31)(32). These results contradict the older studies which did not recommend establishing sex-related reference values (24,(33)(34)(35)(36)(37), except for results found by Pergande and Jung (38).…”
Section: Physiological Determinants Of Cysc Productionmentioning
confidence: 89%
“…Higher values are found in neonates regardless of sex, weight or the child's height (39)(40)(41), including premature infants (35): falling after birth to return to identical values to those in adults by the age of 4 years old (30). Caution is however required in very young children and premature infants in whom high CysC values may reflect low GFR as part of the renal maturation process (35,42).…”
Section: Physiological Determinants Of Cysc Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimates from this investigation are representative of the civilian, noninstitutionalized population of the United States aged 12 to 19 yr in 1988 through 1994. Previous studies of cystatin levels in adolescents have been conducted in relatively small, selected study populations or study populations limited to one institution or ethnicity (7,8,(11)(12)(13). Thus, one of the largest advantages to this study is the generalizability of the results, presenting the distribution of cystatin C levels in a diverse population of race and ethnicity from across the United States.…”
Section: Discussionmentioning
confidence: 99%
“…It has important protective extracellular functions by inhibiting cysteine proteinases, such as papain, ficin, and cathepsins [2], which otherwise cause uncontrolled proteolysis and tissue damage. Serum concentrations of CysC are seemingly independent of sex and muscular mass and constant up to 60 years of age [3,4]. The low molecular weight and positive charge at physiological pH allows CysC to filter freely in the kidney glomerulus with no retrieval back to the circulation, thus serum CysC is a clinically established biomarker for estimating glomerular filtration rate (GFR) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%